ANALISIS YURIDIS PENGATURAN ABORTUS PROVOKATUS TERHADAP KORBAN PEMERKOSAAN DI INDONESIA - Elza Syarief; Lu Sudirman; Tedy Surya; Rina Shahriyani Shahrullah (Fakultas Hukum, Universitas Samudra, 2020)
Abortion or abortus provokatus constitutes a termination of pregnancy before the time of delivery. The objective of the study is to ascertain if the Abortion-related Health Law is a realistic rule based on the health aspects, as well as to analyze how long it should be allowed by the Health Law to perform an abortion according to medical criteria. The study uses a method of normative legal research. It concludes that the Health Law pertaining abortion is a realistic rule based on health aspects. Yet, it is necessary to revise the abortion rules due to rape incidents. The rules permits the abortion if the gestational age is 6 (six) weeks or 40 (forty) days. It is calculated from the first day of the last period. It suggests that the gestational age should be 12 (twelve) weeks or 3 (three) months from the first day of the last period. Keywords: Abortus Provocatus, Legal Protection, Rape Victims